Research of annealing influence on the hardness of detonation coatings from aluminum oxide - Kantay, N.; Rakhadilov, B.K.; Paszkowski, M.; Tuyakbayev, B.; Kurbanbekov, Sh.; Nabioldina, A. (KU Publ., 2021)
The article examines the effect of annealing on the structure and properties of alumina-based coatings obtained by detonation spraying. Coated samples were kept separately at temperatures of 500, 700, 800 and 1200 °C at a pressure of 3.6*10-4 Pa for more than 1 hour. It was found that the microhardness of coatings made of alumina increases by 15-30 % after annealing depending on annealing temperature. The results of nanoindentation show that at 1200 °C the nanohardness of coatings after annealing increases by almost 100%. Aluminum oxide coating is characterized by high strength and density of the coating before and after annealing, and slight porosity. Results of X-ray analysis showed that the alumina powder consists of α-Al2O3 lattice, and after detonation injection coating cubes are converted into a semi-γ-cubic lattice. It was found that during the annealing of the coating at 1200 °C all cells of γ-phase completely transit to the α-phase. It was found that the increase in hardness after annealing of alumina coating at 500, 700, 800 and 1200 °C is associated with an increase in volume fraction of α-Al2O3 phase.
Күйдірудің алюминий оксидінен жасалған детонациялық жабындардың қаттылығына əсерін зерттеу
Исследование влияния обжига на твердость детонационных покрытий из оксида алюминия
Keywords: detonation spraying; aluminum oxide; coating; microstructure; phase; microhardness; indentation; annealing